Maternal, Fetal and Newborn Outcome with Respect to Anemic Status of Women Admitted in Maternity Ward of BPKIHS - Upadhyaya, S; Pokharel, N.; Shrestha, M.; Basnet, P. (Journal of Gandaki Medical College-Nepal, 2019)
Background: Anemia is a common problem in pregnancy particularly in developing countries. In Nepal, the prevalence of anemia in pregnancy is 48%. It is defined by WHO as hemoglobin level less than 11gm/dL in pregnancy. It leads to a number of threats to mother, fetus and newborn. Objectives: The objective of the study was to assess the maternal, fetal and newborn outcome with respect to anemic status of women admitted in maternity ward of BPKIHS, Dharan, Nepal. Methods: A descriptive cross-sectional study was conducted among the 20 to 35 years women admitted in maternity ward of BPKIHS. Total 193 respondents were included in the study by purposive sampling technique. Out of 193 respondents, 78 were anemic and 115 were non-anemic. Maternal, fetal and newborn outcome among all the respondents were assessed by interview and review of records. Pearson Chi-square test was used to find the association between two categorical variables. Results: Maternal outcomes such as preterm delivery, mode of delivery and fetal and newborn outcomes such as abnormal fetal heart rate, IUGR, LBW, low APGAR scores at 1 minute and at 5 minutes, need for resuscitation and need for admission in ward/nursery/NICU were significantly associated with anemic status of women at p value <0.05. The prevalence of anemia among the pregnant women was 40.5%. Conclusion: Maternal outcome such as preterm delivery, cesarean section were associated with anemia. Regarding the fetal and newborn outcome; abnormal fetal heart rate, IUGR, low birth weight, APGAR scores below 7, need for resuscitation, need for admission in ward/ nursery/NICU were associated with anemia.